Wnt Pathway Activation Increases Hypoxia Tolerance during Development - Gersten, Merril (Public Library of Science, 2014)
Adaptation to hypoxia, defined as a condition of inadequate oxygen supply, has enabled humans to successfully colonize high altitude regions. The mechanisms attempted by organisms to cope with short-term hypoxia include increased ATP production via anaerobic respiration and stabilization of Hypoxia Inducible Factor 1α (HIF-1α). However, less is known about the means through which populations adapt to chronic hypoxia during the process of development within a life time or over generations. Here we show that signaling via the highly conserved Wnt pathway impacts the ability of Drosophila melanogaster to complete its life cycle under hypoxia. We identify this pathway through analyses of genome sequencing and gene expression of a Drosophila melanogaster population adapted over >180 generations to tolerate a concentration of 3.5–4% O(2) in air. We then show that genetic activation of the Wnt canonical pathway leads to increased rates of adult eclosion in low O(2). Our results indicate that a previously unsuspected major developmental pathway, Wnt, plays a significant role in hypoxia tolerance.